The introduction of the metric system of weights and measures in the Omsk district in the 1920s - I. V. Makarov (Омский научный вестник: Серия "Общество. История. Современность")
The article is devoted the process metric reform of the 1920s, which is one of the most important parts of the history of Russian and Siberian metrology and an integral part of the socio-economic modernization of the USSR, in the Omsk district. The purpose of the article is to establish the circumstances of the metric reform in the Omsk district, as well as to identify the problems and difficulties that arose during the transition to the metric system of weights and measures. The main sources for writing the article are the files of the funds the Historical Archive of Omsk Region, primarily the fund of the Omsk Chamber of Weights and Measures; the files from State Archive of Novosibirsk Region are also used. The article describes the process of transition to the metric system in the Omsk district through the activities of the district interdepartmental metric commission and the verification chamber of weights and measures. Based on the results of the study, conclusions are drawn about the progress of the metric reform in the Omsk district.